Pemberdayaan Masyarakat dalam Pencegahan dan Penanganan DBD Berbasis Edukasi dan Demonstrasi OVITRAP - de Fretes, Fiane; Rayanti, Rosiana Eva; Raswandaru, Marsela Riska; Patulak, Dazza Lozhera; Anggela, Anggela; Sarwoko, Nazart Tri (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Dengue Hemorrhagic Fever (DHF) is a significant public health issue in tropical regions, including Indonesia. Ledok Village in Salatiga City is one of the endemic areas that shows ongoing proliferation of Aedes aegypti larvae as the primary vector. Although most community members have general awareness of the signs and symptoms of DHF through social media, their understanding of vector control methods, particularly the use of ovitraps, remains low. The purpose of this community engagement activity was to provide education to residents of Ledok Village regarding the signs and symptoms of dengue fever, first aid measures, and preventive efforts, as well as to demonstrate the effective use of ovitraps as a tool to interrupt the life cycle of Aedes aegypti mosquitoes. The health education was delivered through printed media, demonstrations, and a post-test assessment. The post-test results showed that more than 50% of participants demonstrated increased knowledge regarding the symptoms and management of DHF.